The dark side of self-leadership: Do self-leadership strategies deplete energy? - Müller, Teresa; Niessen, Cornelia (50. Kongress der Deutschen Gesellschaft für Psychologie (DGPs), 2016)
This study aims to investigate the depleting characteristics of self-leadership strategies (behavior focused strategies , constructive thought patterns,  Manz, 2015). According to ego-depletion-theory self-control-strength becomes depleted after initial self-regulatory demands and impairs further efforts to exert self-control (e.g. Baumeister, Bratslavsky, Muraven,  & Tice, 1998). To date more than 200 experiments – mostly following the sequential-task paradigm – examined self-regulation and found evidence for the concept of ego depletion (Carter & McCullough, 2014). Building on sequential-task paradigm, we examined ego depletion in the context of  self-leadership at work. As self-leadership is beneficial for work performance and well-being, behavior focused strategies and constructive thought patterns might be demanding and should lead to energy depletion as well. At the canteen of a German university, in a sample of 153 students and employees, we measured ego depletion twice, immediately before and immediately after lunch break with a hand grip task. In addition, participants had to fill out two questionnaires about their work experiences. Hierarchical regression analyses revealed that using constructive thought patterns in the morning was related to higher energy depletion (less time on the hand grip) before lunch. Behavior focused strategies in the morning were associated with higher depletion after lunch when work in the morning was highly demanding. The results of this study indicate that self-leadership might be a double edged sword: Self-leadership is not only a resource in demanding work environments but also demanding itself.